(untitled) (Herald of Journalism, 2020)
In article it is told about use of information communicative means in the modern world. Authors of article give definition to such concepts as «mass media», «mass information», «journalist», define requirements imposed to representatives of the fourth power including importance of knowledge of foreign languages, reveal a big role of information in forma- tion and development of conscious in society. Authors of article carried out questionnaire with 60 respondents for the purpose of studying of use of information technologies by students and defining their level of com- munication.